3D reconstruction of confocal-resolved VGluT1 and VGluT2 clusters and corresponding YFP-labeled apical dendrites. - Yeasmin Akter (7378415) (2025)
Representative 23 × 23 × 2.8 µm reconstructions of confocal channels in apical segments of L5 pyramidal neurons generated by 3D-rendering of 17 optical sections spaced at 170 nm from five-channel confocal/3D-tau-STED imaging of apical dendrites and dendritic spines on L5 pyramidal neurons in S1 of Thy-1-YFP-H mice. YFP-labeled dendrites and spines (white, enhanced by the labeling with GFP antibody), VGluT1 (red, nanobody/Atto 542), and VGluT2 (green, antibody/Alexa Flour 750) were imaged in confocal resolution. Dendrites and clusters were reconstructed using Neurolucida-360 to assign CC and TC synapses to YFP-labeled spines based on their colocalization with VGluT1 or VGluT2, respectively. Still, images of this apical dendrite and spines are shown in Fig 5. (MP4)